أنظار في كتاب "الأجوبة الصغرى لأبي السعود عبد القادر بن علي الفاسي"- دراسة وتحقيق: الأستاذ علي بن أحمد الإبراهيمي - أيت الحيان, حميد (جامعة الوادي - University of Eloued, 2021)
تتغيا هذه الورقة العلمية الكشف عن نماذج من أخطاء المحققين وتصحيفاتهم، وعن بعض الهنات التي تعترض المشتغلين على تحقيق النصوص التراثية، وأبرزها ما تعلق بالمنهج العلمي المتبع في التحقيق. وليس يخفى ما يمكن أن يترتب عن هذا النقص المنهجي، والاضطراب العملي من إساءة وتغيير وتحريف، ولعل عملنا في هذه الدراسة أضرب عن الفرش النظري، واهتم بالجانب التطبيقي، من خلال عمل أكاديمي نال به صاحبه درجة الدكتوراه. ومن خلال تتبعي للنص المحقق وقفت على مجموعة من الملاحظات، وسمتها بأنظار في كتاب الأجوبة الصغرى لأبي السعود عبد القادر الفاسي، رجوت أن تسهم في التنبيه إلى خطورة عملية التحقيق، وضرورة امتلاك المهارات والقدرات والكفايات قبل خوض غمار هذه التجربة. الكلمات المفتاحية: الأجوبة الصغرى – النوازل - أبو السعود –التحقيق Abstract: This scientific paper aims to uncover examples of the errors of the investigators and their corrections, and some of the insults that challenge the practitioners to achieve the traditional texts, most notably related to the scientific method used in the investigation. It is no secret that this systematic deficiency, and the practical turmoil of abuse, change and distortion, may result in the consequences of this study, which is a striking feature of the theoretical brushes, and has taken care of the practical aspect, through the academic work of which has received a doctorate. By following the investigative text, I stood on a set of observations, and i named them with a look in the book of the small answers of Abu Al-Saud Abdul Qadir al-Fassi, i hope to contribute to the alert to the seriousness of the investigation process. Keywords: - traditional texts - Answers - Abu Al-Saud - investigation
Notes In "the Small Answers Of Abu Al-saud Abdul Qadir Bin Ali Al-fassi"-Study And Investigation: Professor Ali Bin Ahmed Brahimi
مقال
Keywords: الأجوبة الصغرى – النوازل - أبو السعود –التحقيق; traditional texts - Answers - Abu Al-Saud - investigation